Estimation of Maize Import Demand Function in Nepal: An ARDL-ECM Approach - Bhattarai, Binod Kumar; Kattel, Rishi Ram; Dhakal, Shiva Chandra; Joshi, Ganesh Raj (Journal of Agriculture and Forestry University, 2026)
This study examined the long-run and short-run determinants of maize import behavior in Nepal, where maize is the second most imported cereal after rice. An error correction version of Autoregressive Distributed Lag (ARDL) model was employed using 28 years of time series data (1997-2024) collected from secondary sources. The stationarity of variables was tested using Augmented Dickey-Fuller (ADF) test, Phillips-Perron (PP) and Kwiatkoski-Phillips-Schmidt- Shin (KPSS) tests, confirming integration at either I (0) or I (1). The Bounds test verified the existence of long-run relationships among the variables (F=11.18, p